2016
DOI: 10.3389/fcell.2016.00124
|View full text |Cite
|
Sign up to set email alerts
|

Septins As Modulators of Endo-Lysosomal Membrane Traffic

Abstract: Septins constitute a family of GTP-binding proteins, which assemble into non-polar filaments in a nucleotide-dependent manner. These filaments can be recruited to negatively charged membrane surfaces. When associated with membranes septin filaments can act as diffusion barriers, which confine subdomains of distinct biological functions. In addition, they serve scaffolding roles by recruiting cytosolic proteins and other cytoskeletal elements. Septins have been implicated in a large variety of membrane-dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 34 publications
2
26
0
Order By: Relevance
“…molecular scaffolds (Joo, Surka, & Trimble, 2007). Septins have previously been implicated in processes such as cytokinesis in budding yeast (Kim, Haarer, & Pringle, 1991) and mammalian cells (Surka, Tsang, & Trimble, 2002), microbial infection (Phan et al, 2013;Torraca & Mostowy, 2016), phagocytosis (Huang et al, 2008) and endo-lysosomal sorting (Song, Russo, & Krauss, 2016). Septins play a role in the internalisation of bacterial pathogens including Listeria monocytogenes (Pizarro-Cerda et al, 2002), and here, we demonstrate a role for septins in the S. Typhimurium invasion process.…”
supporting
confidence: 61%
See 1 more Smart Citation
“…molecular scaffolds (Joo, Surka, & Trimble, 2007). Septins have previously been implicated in processes such as cytokinesis in budding yeast (Kim, Haarer, & Pringle, 1991) and mammalian cells (Surka, Tsang, & Trimble, 2002), microbial infection (Phan et al, 2013;Torraca & Mostowy, 2016), phagocytosis (Huang et al, 2008) and endo-lysosomal sorting (Song, Russo, & Krauss, 2016). Septins play a role in the internalisation of bacterial pathogens including Listeria monocytogenes (Pizarro-Cerda et al, 2002), and here, we demonstrate a role for septins in the S. Typhimurium invasion process.…”
supporting
confidence: 61%
“…Septins have the ability to oligomerise into filaments and higher order structures (Kinoshita, Field, Coughlin, Straight, & Mitchison, ) in order to perform cellular functions such as microtubule stabilisation (Nagata et al, ), actin bundling (Schmidt & Nichols, ), as well as the formation of membrane diffusion barriers (Barral, Mermall, Mooseker, & Snyder, ), and molecular scaffolds (Joo, Surka, & Trimble, ). Septins have previously been implicated in processes such as cytokinesis in budding yeast (Kim, Haarer, & Pringle, ) and mammalian cells (Surka, Tsang, & Trimble, ), microbial infection (Phan et al, ; Torraca & Mostowy, ), phagocytosis (Huang et al, ) and endo‐lysosomal sorting (Song, Russo, & Krauss, ). Septins play a role in the internalisation of bacterial pathogens including Listeria monocytogenes (Pizarro‐Cerda et al, ), and here, we demonstrate a role for septins in the S .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, ErbB2 interacts with a de-ubiquitylating enzyme USP9x (Marx et al, 2010; Marcus et al, 2016) that has been shown to protect ErbB2 from bortezomib-induced lysosomal degradation (Marx et al, 2010). In addition, septins play critical roles in endocytosis and exocytosis (Beites et al, 1999, 2005; Maimaitiyiming et al, 2013; Phan et al, 2013; Tokhtaeva et al, 2015; Song et al, 2016), and disruption of septin dynamics with FCF may induce ErbB2 internalization or delay its recycling to the plasma membrane.…”
Section: Septins Stabilize Receptor Tyrosine Kinasesmentioning
confidence: 99%
“…First, they interact with components of endocytosis and exocytosis machinery (Beites et al, 1999, 2005; Amin et al, 2008; Maimaitiyiming et al, 2013; Phan et al, 2013; Tokhtaeva et al, 2015; Song et al, 2016). Second, they may regulate the interaction between transmembrane proteins and cytoskeletal proteins (Gilden and Krummel, 2010; Hagiwara et al, 2011; Hall and Russell, 2012; Mostowy and Cossart, 2012; Bridges et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This interaction with PIs supposedly mediates septin membrane association, which is a determinant factor for the structural and functional features of the protein (Pan et al, 2007;Zhang et al, 1999;Tanaka-Takiguchi et al, 2009;Casamayor and Snyder, 2003). Septins associate with a variety of PIs at different intracellular membranes (Zhang et al, 1999;Akil et al, 2016;Dolat and Spiliotis, 2016;Pagliuso et al, 2016), and control numerous cellular functions such as cytokinesis, cilogenesis, vesicular trafficking, cell polarity and lipid droplet formation (Fung et al, 2014;Oh and Bi, 2011;Song et al, 2016;Balla, 2013;Gassama-Diagne and Payrastre, 2009;Gassama-Diagne et al, 2006;Akil et al, 2016;Schink et al, 2016).…”
Section: Introductionmentioning
confidence: 99%